DESCRIPTION OF CLINICAL AND PARACLINICAL RESULTS OF LAPAROSCOPIC RETROPERITONEAL RESECTION OF BENIGN ADRENAL ADENOMA AT VIET DUC FRIENDSHIP HOSPITAL IN 2018 (Vietnam Journal of Community Medicine, 2021)
The study was conducted with objectives: Describe the clinical and paraclinical results of laparoscopic retroperitoneal resection of benign adrenal tumors at Viet Duc Friendship Hospital in 2018 on 67 patients diagnosed as benign adrenal tumor and was treated with retroperitoneal endoscopic surgery at Viet Duc hospital in 2018. The study design was retrospective.  Results: The clinical syndromes of the patients were mainly Cushing's syndrome (3%), Conn's syndrome (29,8%), Pheochromocytome (17,9%) and 49,3% of patients with nonsecretory tumors. . Specific biochemical tests: hypercortisolemia (4,48%); increased blood catecholamines (16,42%) and increased urinary catecholamines (14,93%). Ultrasound: The average tumor size was 20.37 ± 16.05mm; The diagnostic sensitivity was 74,6%. CT or MRI: The mean tumor size was 26.63 ± 12.7mm; highly sensitive and is the gold standard on diagnostic imaging. Conclusion: The clinical and laboratory results of patients undergoing laparoscopic resection of benign adrenal tumors are highly sensitive.
Keywords: Laparoscopic, retroperitoneal resection of benign adrenal adenoma